Analysis of loss on single-phase dry transformers with non-linear load - Khristiana, Harrij Mukti; Soeparman, Sudjito; Wahyudi, Slamet; Hasanah, Rini Nur (Eastern-European Journal of Enterprise Technologies, 2021)
The paper studies power losses in transformers due to non-linear loads. The research aims to analyze the power loss in a single-phase dry transformer under a non-linear load. The research uses an SW43W Power supply type, FlukeView Power Quality Analyzer as a DC or AC power supply on the primary side of the transformer. The non-linear load is connected to the secondary side. The loading test of the dry transformer was carried out at non-linear loads. The load variations used 0 %; 12.5 %; 25 %; 37.5 %; 50 %; 62.5 %; 75 %; 87.5 % and 100 %, as well as variations in the THD value by adjusting the ignition angle (α). The non-linear loads used are Half-Wave Rectifier and Controlled Half-Wave Rectifier with resistive loads with variations in THD values. The results showed that the transformer losses comprised Pno load and Pload. The operation of the transformer with constant input voltage and frequency with THDv<5 % resulted in a constant Pno load value at all load values. The greater the percentage of the load, the higher the load. The increase in THD because of non-linear load will increase the load on the transformer. The value of the derating factor is obtained by connecting the increase in losses (∆PLosses), which is influenced by THD and the increase in temperature T(°C) in dry transformers. When the transformer is loaded with a non-linear load, the derating factor<1. THD and derating factor form a linear relationship, when THD increases, the derating factor value decreases. Linear load on the transformer causes a decrease in its capacity, but if it gets a non-linear load with THD=39.1 %, it can withstand a load of 84.294 %, besides the increase in total harmonic distortion will increase losses and reduce transformer capacity